Efficacy analysis of enhanced recovery after surgery in laparoscopic-assisted radical resection of type I choledochal cyst - Zhang, Bing; Fang, Yifan; Wu, Dianming; Xie, Siqi; Fang, Xuejuan (Frontiers in Pediatrics, 2023)
Objective The objective of this study was to investigate the feasibility and effectiveness of laparoscopic-assisted radical resection of type I choledochal cyst (CC) guided by the principles of enhanced recovery after surgery (ERAS). Methods A retrospective cohort study of type I CC admitted to our hospital between May 2020 and December 2021 were analyzed, a total of 41 patients with choledochal cyst underwent surgery during this period and 30 cases were selected based on inclusion and exclusion criteria. Patients (n = 15) who received the traditional treatment from May 2020 to March 2021 were included in the traditional group. Patients (n = 15) who received ERAS from April 2021 to December 2021 were included in the ERAS group. Both groups underwent surgery performed by the same surgical team. Preoperative data of the two groups were recorded, and relevant data were statistically analyzed and compared. Results There was a statistically significant difference in the dose of opioids. Significant differences were observed between the ERAS and traditional groups in the results of the FLACC pain assessment scale on the 1st and 2nd day after surgery, time of gastric tube, urinary catheter and abdominal drainage tube removal, time of first defecation after operation, time of first eating after operation, time to reach full food intake, results of CRP, ALB, and ALT on the 3rd and 7th postoperative day, postoperative hospital stay, and total treatment cost. No significant differences were observed between the two groups in terms of gender, age, body weight, cyst size, preoperative CRP, ALB, ALT, intraoperative blood loss, operation time, and the number of cases converted to laparotomy. Neither the FLACC pain assessment scale on the 3rd day after surgery, the incidence of postoperative complications, nor the rate of readmission within 30 days showed significant differences. Conclusions Laparoscopic-assisted radical resection of type I CC guided by the principles of ERAS is safe and effective for children. The ERAS concept demonstrated advantages over traditional laparoscopic surgery, including reduced opioid use, shorter time to first postoperative defecation, earlier resumption of postoperative feeding, shorter time to reach full feeding, shorter postoperative hospital stay, and lower total treatment cost.